PENGARUH RESPONSIBILITAS, EMPATI, RELIABILITAS PENGURUS TERHADAP LOYALITAS ANGGOTA KOPERASI BUMI KRESNA - Yunus . (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2021)
The Bumi Kresna Cooperative Management as the manager in charge of providing services to members of the Bumi Kresna Cooperative in running the cooperative's economy. Services provided by the management so far are still less responsive to the needs of consumer goods and clothing needed by members. The empathy that is carried out by the management is often an obstacle and becomes a talk among members. The reliability of the management in routine service activities is often not according to the appointments or schedules. The ability to provide services that are not up to standard will have an impact on members in conducting transactions, reducing loyalty as customers which results in problematic member loyalty. This research is focused on the Effect of responsibility, empathy, management reliability on loyalty of the Kresna Bumi cooperative members